Beyond AI: the crisis of Organoid Intelligence questions between the dilemma over consciousness and scenarios of unpredictability (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Organoid Intelligence exploits the use of human-machine interface technologies to develop AI systems and to explore the potential of synthetic biology using brain organoids. Their ability to replicate brain functions raises the possibility of creating tissues with an uncertain form of consciousness and the potential faculty to feel pain or pleasure. This issue will be analyzed not only from the different types of “conscious experiences” that could be traced back to organoids, but also from the multifaceted concept of consciousness itself and the related application of the precautionary principle, highlighting scenarios of unpredictability as a reverberation of questions about consciousness.
Keywords: Organoid Intelligence; organoids; consciousness; precautionary principle; unpredictability